Neuroendocrine differentiation of prostate cancer leads to PSMA suppression. Issue 2 (February 2019) - Bakht, Martin K; Derecichei, Iulian; Li, Yinan; Ferraiuolo, Rosa-Maria; Dunning, Mark; Oh, So Won; Hussein, Abdulkadir; Youn, Hyewon; Stringer, Keith F; Jeong, Chang Wook; Cheon, Gi Jeong; Kwak, Cheol; et al.
Abstract : Prostate-specific membrane antigen (PSMA) is overexpressed in most prostate adenocarcinoma (AdPC) cells and acts as a target for molecular imaging. However, some case reports indicate that PSMA-targeted imaging could be ineffectual for delineation of neuroendocrine (NE) prostate cancer (NEPC) lesions due to the suppression of the PSMA gene ( FOLH1 ). These same reports suggest that targeting somatostatin receptor type 2 (SSTR2) could be an alternative diagnostic target for NEPC patients. This study evaluates the correlation between expression of FOLH1, NEPC marker genes and SSTR2 . We evaluated the transcript abundance for FOLH1 and SSTR2 genes as well as NE markers across 909 tumors. A significant suppression of FOLH1 in NEPC patient samples and AdPC samples with high expression of NE marker genes was observed. We also investigated protein alterations of PSMA and SSTR2 in an NE-induced cell line derived by hormone depletion and lineage plasticity by loss of p53. PSMA is suppressed following NE induction and cellular plasticity in p53-deficient NEPC model. The PSMA-suppressed cells have more colony formation ability and resistance to enzalutamide treatment. Conversely, SSTR2 was only elevated following hormone depletion. In 18 NEPC patient-derived xenograft (PDX) models we find a significant suppression of FOLH1 and amplification of SSTR2 expression. Due to the observed FOLH1 -supressed signature of NEPC, this study cautions on the reliability of using PMSA as a target for molecular imaging of NEPC. The observed elevation of SSTR2 in NEPC supports the possible ability of SSTR2-targeted imaging for follow-up imaging of low PSMA patients and monitoring for NEPC development.